Minimally Invasive vs. Open Surgery for Hallux Valgus: A Meta-Analysis - Ji, Linfeng; Wang, Ketao; Ding, Shenglong; Sun, Chengyi; Sun, Songmin; Zhang, Mingzhu (Frontiers in Surgery, 2022)
Purpose: In recent years, minimally invasive surgery (MIS) for hallux valgus has emerged and gained popularity. To date, the evidence on the benefits of MIS for hallux valgus is still controversial. This updated meta-analysis aimed to comprehensively evaluate the efficiency of the MIS versus open surgeries for hallux valgus. Methods: A systematic literature search of PubMed, Embase and the Cochrane Library was performed. Two independent reviewers conducted data extraction and analyzed data with R software. Data were presented with risk ratio (RR) and standardized mean difference (SMD) along with 95% confidence interval (CI). Results: Twenty-two studies in which there were 790 feet treated with MIS procedure and 838 feet treated with open procedure were included. The correction of sesamoid position was better in the MIS group. The postoperative distal metatarsal articular angle (DMAA) of MIS group was lower. There was less pain at the early phase in the MIS group. The MIS group had shorter surgery time and shorter hospitalization time compared with the open group. Our meta-analysis revealed no statistically significant difference in hallux valgus angle (HVA), first intermetatarsal angle (IMA), the first metatarsal shortening, the American Orthopaedic Foot and Ankle Society (AOFAS) score, visual analog scale (VAS) score at the final follow-up or complication rate (when all studies were considered). When taking into consideration only randomized controlled trial, the AOFAS score was higher in the MIS group while HVA, IMA, DMAA and complication rate remained no significance. Postoperative IMA of MIS group was significantly lower when only studies reporting the second generation MIS were included. When just studies adopted the third generation MIS were included, the HVA and DMAA were lower in the MIS group. Conclusion: The MIS procedures were more effective than open surgeries in the treatment of hallux valgus. Moreover, the MIS group achieved better radiologic and clinical outcomes compared with open group.